2009
DOI: 10.1080/00958970802233110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectral and biological investigations of 5(2′-hydroxyphenyl)-3-(4-substituted-phenyl) pyrazolinates of cobalt(II) and their addition complexes with N, P donor ligands

Abstract: 5(2 0 -Hydroxyphenyl)-3-(4-substituted-phenyl)pyrazolinates of cobalt(II) of the type (C 15 H 12 N 2 OX) 2 Co [here substituted group X is -H, -Cl, -CH 3 or -OCH 3 ] have been synthesized by reaction of anhydrous cobalt(II)chloride with the sodium salt of the pyrazolines in 1 : 2 molar ratio. Their addition complexes with N and P donor ligands [2, 2 0 -bipyridine, 1, 10-phenanthroline and triphenylphosphine] were prepared in 1 : 1 molar ratio. The newly synthesized complexes were characterized by elemental ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Additionally, when all the antimicrobial MIC values were compared, the ligand and Cu(II) complex displayed the highest antimicrobial efficacy with MIC values ranging between 20-40 mg mL À1 . Accordingly, the data obtained from this investigation were in good agreement with the previous studies that expressed the metal complexes with Schiff bases have greater activity toward microorganisms [7][8][9]. Finally, it suggested that the reason for this higher antimicrobial efficacy can be related to the inhibition several structural enzymes, which play a key role in vital metabolic pathways of the microorganisms.…”
Section: Mass Spectrasupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, when all the antimicrobial MIC values were compared, the ligand and Cu(II) complex displayed the highest antimicrobial efficacy with MIC values ranging between 20-40 mg mL À1 . Accordingly, the data obtained from this investigation were in good agreement with the previous studies that expressed the metal complexes with Schiff bases have greater activity toward microorganisms [7][8][9]. Finally, it suggested that the reason for this higher antimicrobial efficacy can be related to the inhibition several structural enzymes, which play a key role in vital metabolic pathways of the microorganisms.…”
Section: Mass Spectrasupporting
confidence: 91%
“…The results of this investigation revealed that the ligand, Cu(II), Ni(II) and Co(II) complexes possessed higher antimicrobial activity, although it was generally reported that free ligands shown lower activity than complexes [7][8][9]27,28]. Additionally, when all the antimicrobial MIC values were compared, the ligand and Cu(II) complex displayed the highest antimicrobial efficacy with MIC values ranging between 20-40 mg mL À1 .…”
Section: Mass Spectramentioning
confidence: 86%
See 1 more Smart Citation